Sistematik Literatur Review (SLR) Pengaruh Model Pembelajaran terhadap Kemampuan Komunikasi Matematika Siswa - Khairul Wajdi; Baharidi Ahmad Habib; Novan Ardiyansyah; Nani Kurniati (Yayasan Arfah Bin Haji Muhammad Saleh, 2026)
This study aims to examine the influence of various learning models on students' mathematical communication skills through a systematic literature review (SLR) approach. This method is used to identify, evaluate, and interpret the entire research relevant to the specified topic. The search was carried out on scientific articles published in the period 2013–2023 from various accredited national journals and proceedings. Based on the inclusion and exclusion criteria, as many as 20 selected articles were analyzed in depth. The results of the analysis show that the Realistic Mathematics Education (RME), Connecting-Organizing-Reflecting-Extending (CORE), and scientific approaches have consistently had a positive impact on improving students' mathematical communication skills. Some studies have also combined RME with ethnomathematical contexts that show more effective results in improving overall aspects of mathematical communication, including the ability to convey ideas, formulate arguments, and interpret and present mathematical information. Thus, it can be concluded tentatively that constructivism-based learning models that are contextual and involve students' active participation tend to be more effective in developing their mathematical communication skills.